Parents' Strategies for Enhancing Counting Skills in 5-6-Year-Old Children - Erawati, Ni Ketut (Exploration in Early Childhood Research, 2024)
This study explores parents' strategies to support their 5-6-year-old children's understanding of counting. The research adopts a qualitative descriptive design, allowing for an in-depth understanding of parents' experiences and practices through interviews and live observations. The informants are parents from a private kindergarten (TK) in Jakarta, Indonesia, who actively teach their children counting activities. The findings reveal that parents utilize three main strategies: mathematics discussions, integrating numeracy into daily activities, and using educational games such as 'Monopoly' or digital applications like 'ABC mouse'. These strategies help children develop their understanding of basic mathematical concepts naturally and enjoyably. The results have significant implications for early childhood education. The practices adopted by parents have proven effective in enhancing children's mathematical comprehension. Integrating numeracy into everyday activities allows children to connect mathematical concepts with real-life situations, while mathematical conversations enrich their learning experiences. The use of educational games also facilitates engaging and interactive math learning. Based on these findings, it is recommended that parents and educators continue to promote these strategies to support early childhood mathematical learning and develop resources to facilitate their implementation. With a holistic and integrated approach, this research can provide children with a solid mathematical foundation for future success in learning mathematics.